Slave agriculture and financial markets in antebellum America: the Bank of the United States in Mississippi, 1831-1852 - Kilbourne, Richard Holcombe (Pickering & Chatto, 2006)
"Slave Agriculture and Financial Markets marks an important chapter in the study of antebellum southern slavery and the credit system. Using the Mississippi branch of the Second Bank of the United States as a case study, Kilbourne analyses the way intermediaries, such as chartered banks and commercial partnerships, were used to finance slave agriculture. he details how the Bank supported the nation's credit abroad by providing apparently limitless credit facilities to Southern planters along the Mississippi river. This ground-breaking new book draws heavily on major archives which have never been studied before."--Jacket.
Keywords: Business History and race